Axenfeld–Rieger Syndrome: A Case Report and Brief Review - Amina Sultan; Simran Uppal; Akanksha Juneja (Journal of South Asian Association of Pediatric Dentistry)
Axenfeld–Rieger Syndrome (ARS) is a rare autosomal dominant genetic disorder with an overall incidence of 1:200,000 that has mainly ocular, periumbilical, and dental abnormalities like oligodontia/hypodontia, microdontia, and delayed eruption of permanent teeth. Its management requires a multidisciplinary approach involving a team of dentists, ophthalmologists, cardiologists, and general physicians, along with regular follow-up. Pediatric dentists play a crucial role in such patients, as a timely diagnosis could prevent ocular complications such as glaucoma in later stages. This paper presents a case report with the classical signs and symptoms of ARS in a 12-year-old female patient demonstrating oligodontia, microdontia, and short roots.